Mycorrhizal Bio-fertilizer An effective tool to manage abiotic stress in crop plants - Dev, Rahul; Dayal2, Devi; Singh, Traloki (Indian Farming, 2018)
Role of AMF in alleviating abiotic stress in plants has been consistently demonstrated specially on arid and semi-arid crop species by various workers. The proper use of AMF in major crops will be a boon in managing abiotic stress and making cropping system sustainable/ profitable in fragile ecosystem of arid and semi-arid regions.